2019
DOI: 10.7717/peerj.6572
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and conservation in a warm North American desert: effect in shrubby plants

Abstract: Background Deserts are biologically rich habitats with a vast array of animals and plants adapted to xeric conditions, and most deserts are among the planet’s last remaining areas of total wilderness. Among North American deserts, the Chihuahuan Desert has the highest levels of diversity and endemism. To understand the effect of future climate change on plants distributed in this arid land and propose effective conservation planning, we focused on five endemic shrubby species that characterize the Chihuahuan D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…Habitat and biodiversity loss are global concerns related to climate change-especially drought-and serve as an enormous warnings for the future [1][2][3]. Based on a continuous rate of global warming, a temperature increase of~4 • C is anticipated in tropical zones and a mean global temperature increase of~2.5 • C is anticipated by 2100 AD [4,5], which, in turn, changes the habitat of species.…”
Section: Introductionmentioning
confidence: 99%
“…Habitat and biodiversity loss are global concerns related to climate change-especially drought-and serve as an enormous warnings for the future [1][2][3]. Based on a continuous rate of global warming, a temperature increase of~4 • C is anticipated in tropical zones and a mean global temperature increase of~2.5 • C is anticipated by 2100 AD [4,5], which, in turn, changes the habitat of species.…”
Section: Introductionmentioning
confidence: 99%
“…As a consensus, the future climate change models show a restriction in future distribution for Manihot walkerae with the lowest loss of distribution calculated as −2.08% for the year 2050 with an RCP of 8.5, and the highest, −14.37%, for the year 2070 with an RCP of 4.5, whereas for two of the future climate change scenarios at an RCP of 4.5 for the year 2050, it is predicted that there could be a potential increase of approximately 7% in distribution (Table 2). Similarly, another SDM study conducted in the Chihuahan desert found that some endemic plants were shown to be affected by climate change and expanded in distribution [48]. The areas that were shown to be most affected by climate change were those in the northeastern and southernmost portions of the Tamaulipan Thornscrub ecoregion (Figures 3-5).…”
Section: Discussionmentioning
confidence: 80%
“…Some limitations of our study are that we relied solely on bioclimatic variables for our modeling and that we used a small number of occurrences to create our models. Using bioclimatic variables for climate change modeling is common and has been used to model the effects of climate change on the distribution of different species of plants and animals, some of which are endangered and restricted [23,48,49]. Including static topographic variables could have improved the reliability of our models, but in some instances, such as when topographic variables like elevation and bioclimatic variables are highly correlated, they could hinder the statistic reliability of the model [50].…”
Section: Discussionmentioning
confidence: 99%